A new species of Pristimantis (Amphibia, Anura, Craugastoridae) from the foothills of the Andes in Manu National Park, southeastern Peru - Shepack, Alexander (2016)
We describe a new species of Pristimantis from the humid sub-montane forest of the Región Cusco in Peru. Pristimantis pluvialis sp. n. was collected in the Kosñipata and Entoro valleys at elevations from 740 to 1110 m a.s.l., near the borders of Manu National Park and within the Huachiperi Haramba Queros Conservation Concession. The new species can be distinguished from other members of the genus Pristimantis by its rostral tubercle, smooth dorsal skin, and by its advertisement call. Pristimantis lacrimosus and P. waoranii superficially most resemble the new species, but P. pluvialis sp. n. differs from both species by having a rostral tubercle (absent in P. waoranii and variable in P. lacrimosus) and larger size, from P. lacrimosus by its call emitted at a lower frequency, and from P. waoranii for its dorsal coloration with dark markings. Two other species have partially overlapping distributions and resemble the new species, P. mendax and P. olivaceus, but they produce advertisement calls with much higher dominant frequencies than the advertisement call of the new species. Furthermore, P. mendax differs from the new species by lacking a rostral tubercle and by having a sigmoid inner tarsal fold, whereas P. olivaceus differs by being smaller and by having dorsal skin shagreen with scattered tubercles. The new species has snout-vent length of 21.8–26.9 mm in males (n = 12) and 28.8 mm in a single female.